Effects of different doses of tramadol added to levobupivacaine in continuous wound infusion for postoperative pain treatment following cesarean section. (1st February 2017) - Ekmekçi, Perihan; Çağlar, Gamze S.; Yilmaz, Hakan; Kazbek, Baturay K.; Gursoy, Asli Yarci; Kiseli, Mine; Tüzüner, Filiz
Abstract: Objective : The aim of this study was to compare the effects of two different doses of tramadol added to levobupivacaine as continuous wound infusion, on VAS scores following cesarean section. Methods : The study was conducted in an University Hospital and was approved by the Local Ethical Committee. Sixty-five ASA I-II parturients, between 18 and 45 years were enrolled. The participants were randomized to three groups. Group T1 ( n = 21) was given the study solution consisting of levobupivacaine 0.25% + tramadol 1 mg/kg. Group T2 ( n = 21) was given levobupivacaine 0.25% + tramadol 2 mg/kg and Group L ( n = 21) was given levobupivacaine 0.25%, subcutaneously, alone. Each patient who delivered by cesarean section was applied a triple orifice epidural catheter above rectus fascia for continious wound infiltration. VAS at rest and with 20 degrees leg lift, time to first additional analgesic, total additional analgesic consumption, side effects, and sedation scores were recorded. Results : There were no statistically significant differences among groups, concerning VAS scores at rest and VAS scores at leg lift. Total amount of additional analgesics and sedation scores were also similar for three groups. Conclusion : Different doses of tramadol as adjunct to local anesthetics in continuous wound infiltration following cesarean section do not seem to provide superior analgesia.